Examining Positive and Negative Impacts of Artificial Intelligence in English as a Foreign Language Learning: A Case Study at IAIN Parepare - Mujahidah; Asni, Yulie; Muallim, Muajiz; Sardi, Ahmed; Suherman (Association of Language Teachers in Southeast Asia (ALTSA), 2026)
This research examines students' perceptions of Artificial Intelligence (AI) in learning English as a Foreign Language (EFL), focusing on their views regarding its benefits and challenges. Conducted at the English Language Education Study Program, Tarbiyah Faculty, IAIN Parepare, this study involved 30 students selected through random sampling to ensure generalizability. A qualitative approach was employed, utilizing structured interviews and Focus Group Discussions (FGDs) to gather insights into students’ experiences with AI tools such as Elsa Speak, Duolingo, and Google Assistant. Data were analyzed thematically to identify recurring themes and key perspectives. The findings revealed that students perceive AI as both advantageous and limiting in their EFL learning journey. On the positive side, AI was seen as increasing motivation, boosting confidence in speaking, and providing practical opportunities for self-directed learning. However, students also expressed concerns regarding overreliance on AI tools, decreased creativity in language production, and AI's inability to adapt to individual learning styles and personalities. Additionally, some participants worried about AI’s potential impact on future job opportunities. The study concludes that while students generally view AI as a valuable aid in EFL learning, they recognize the need for a balanced approach. Educators and learners should integrate AI with traditional learning methods to enhance effectiveness while minimizing its limitations. Future research should further explore students' long-term perceptions of AI and its role in diverse EFL learning contexts.